(untitled) (Journal of the College of Basic Education, 2023)
In this paper, Chebyshev Operational matrices of Integration (first and second) for the approximate solutions of Variational problems are introduced. The main idea behined this approach is that it reduced such problems to ones of solving systems of algeric equations using spectral method. Only a small number of Chebyshev wavelets are needed to obtain a satisfactory results. The applications of the proposed method are demonstrated through illustrative examples.